Endometrial Tuberculosis: Hysteroscopic Findings of a Clinical Case - Daniela Siqueira Prado; Lucas Félix Cardoso; Raimundo Dantas de Maria Júnior; Guilherme Machado de Santana; Israel Santos Marcelo; Marcela Sampaio Lima; Ângela Maria Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Endometrial tuberculosis is a rare diagnosis in the postmenopausal period, and it can mimic a carcinoma. The present article describes the case of a 54-year-old female patient with weight loss, abdominal pain, and ascites. An ultrasonography showed endometrial thickening, and a video hysteroscopy revealed a uterine cavity with formations with cotton aspect covering the entire endometrial surface and the tubal ostia. An anatomopathological evaluation diagnosed endometrial tuberculosis. The treatment was with a standardized therapeutic scheme (ethambutol, isoniazid, pyrazinamide and rifampicin), and the patient evolved with clinical improvement and normal uterine cavity at hysteroscopy. Considering the lack of pathognomonic hysteroscopic findings of the disorder, it is important to disclose the images of the case.